2009
DOI: 10.1038/nmeth.1296
|View full text |Cite|
|
Sign up to set email alerts
|

A bright and photostable photoconvertible fluorescent protein

Abstract: Photoconvertible fluorescent proteins offer significant potential as tools for investigating dynamic processes in living cells and for emerging super-resolution microscopy techniques. Unfortunately, most probes in this class are hampered by oligomerization, small photon budgets, or poor photostability. Here we report an EosFP variant that functions well in a broad range of protein fusions for dynamic investigations, exhibits high photostability, and preserves the superior ~10-nm localization precision of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
489
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(523 citation statements)
references
References 16 publications
14
489
1
3
Order By: Relevance
“…In an earlier paper (27), we have reported that H-NS appears as a few large and discrete clusters in cells when fused to mEos2, a previously reported monomeric version of the Eos fluorescent protein (14,16). We also observed similar results when H-NS was fused to PAmCherry (27), another previously reported monomeric PAFP.…”
Section: Dimerization Tendency Of Photoactivatable Fluorescent Proteinssupporting
confidence: 82%
See 1 more Smart Citation
“…In an earlier paper (27), we have reported that H-NS appears as a few large and discrete clusters in cells when fused to mEos2, a previously reported monomeric version of the Eos fluorescent protein (14,16). We also observed similar results when H-NS was fused to PAmCherry (27), another previously reported monomeric PAFP.…”
Section: Dimerization Tendency Of Photoactivatable Fluorescent Proteinssupporting
confidence: 82%
“…Here, we compare four properties of PAFPs that are critical for superresolution imaging and report two new PAFPs that exhibit excellent performance in all four properties. (14), mEos3.2 (15), tdEos (16), mKikGR (17), PAmCherry (18), PAtagRFP (19), mMaple (20), PSCFP2 (13,21), Dronpa (22), and mGeosM (23). From this screen, we found that none of these PAFPs was simultaneously optimal in all four criteria described above.…”
mentioning
confidence: 88%
“…Given its relatively long absorption maxima and excellent photophysics, we then tested the utility of caged SiRh Q with mEos24a in multicolor localization microscopy. To evaluate the cross‐talk between the two labels, we expressed a fusion protein containing mEos2 and a mitochondrial localization sequence and then stained F‐actin with phalloidin conjugate 17 .…”
mentioning
confidence: 99%
“…The foci were also visible as hotspots using the green-red photoswitchable fluorescent protein mEos2 [60] excited by super-resolution stochastic optical reconstruction microscopy (STORM) (Figure 1(c)), with modeling using 3C structural data of the yeast chromosome [61] and sequence alignment analysis for the location of Mig1 target promoters supporting the hypothesis that the majority of Mig1 clusters were specifically binding to Mig1 target genes.…”
Section: Resultsmentioning
confidence: 79%